The effect and safety of corticosteroid treatment for severe community-acquired pneumonia: a meta-analysis of randomized controlled trials - Chen, Yang; Kuang, Huanming; Zhu, Youfeng; Luo, Xing (Frontiers in Medicine, 2024)
Background There is ongoing debate on the efficacy and safety of corticosteroid therapy for severe community-acquired pneumonia (sCAP). Our aim was to investigate the safety and therapeutic effectiveness of corticosteroids in the sCAP therapy. Methods Electronic databases (Cochrane Library, PubMed, Web of Science and Embase) were searched from inception to January 10, 2024. We examined for randomized controlled studies assessing the effectiveness and safety of corticosteroid therapy in individuals with sCAP. The primary outcome was short-term mortality. Subgroup analyses were carried out according to the corticosteroid type. Additionally, trial sequential analysis (TSA) was carried out. Results In total, 11 trials, including 1959 patients, met the predetermined standards and underwent analysis. Overall, our meta-analysis exhibited that corticosteroids may considerably lower short-term mortality when compared to control treatment [6 studies (1,582 patients); odds ratio (OR), 0.65; 95% confidence interval (CI) 0.49–0.88; p = 0.005] and C-reactive protein (CRP) levels [5 studies (359 patients); mean difference (MD), −6.97; 95% CI −12.33 to −1.60; p = 0.01], but TSA revealed that the sample size needs to be larger. Moreover, we observed that corticosteroids reduced the hospital length of stay [7 studies (999 patients); MD, −3.56; 95% CI, −4.28 to −2.84; p < 0.001], need for mechanical ventilation (MV) [7 studies (1,328 patients); OR, 0.60; 95% CI, 0.45–0.79; p = 0.001] and MV duration [4 studies (736 patients); MD, −5.62; 95% CI, −7.31 to −3.94; p < 0.001], which was in agreement with TSA. However, adverse events, length of hospital and intensive care unit (ICU) stay were not evidently shortened when TSA was utilized. Furthermore, subgroup analysis revealed that all of the above studies benefited from hydrocortisone treatment in comparison to the control group. Conclusion Our meta-analysis revealed that corticosteroids, especially hydrocortisone, could decrease the mortality of individuals with sCAP. Systematic review registration [https://clinicaltrials.gov/], identifier [CRD42023415555].